Time of day influences the environmental effects on muscle force and contractility - Racinais, S.; Blonc, S.; Jonville, S.; Hue, O. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To investigate the effects of environmental temperature and the diurnal increase in body temperature on muscle contractile processes, 11 male subjects performed maximal and submaximal isometric contractions of the knee extensors with recording of the electromyographic activity in four different conditions (morning/neutral, morning/moderately warm and humid, afternoon/neutral, and afternoon/moderately warm and humid).